2004
DOI: 10.1080/07408170490426116
|View full text |Cite
|
Sign up to set email alerts
|

Economic design of a variable sampling rate EWMA chart

Abstract: A Variable Sampling Rate (VSR) control chart is a control chart whose sampling scheme is to vary the sampling interval and the sample size for the next sample depending on the current chart statistic. A VSR EWMA chart is an EWMA chart with the VSR sampling scheme. An economic model, which was developed for a VSRX chart, is also applied here to evaluate the efficiency of the VSR EWMA chart. The properties of the VSR EWMA chart are obtained by using a Markov chain approach. The model contains cost parameters whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…Hence, a shorter sampling interval helps to constrain the quality related costs which increase with shift sizes. We also remark that, in previous research optimal sampling interval is observed to decrease with shift size for an EWMA mean chart (Park et al, 2004), which is in consistence with our results for the EWMA-m/EWMA-v scheme.…”
Section: Numerical Examplessupporting
confidence: 78%
See 2 more Smart Citations
“…Hence, a shorter sampling interval helps to constrain the quality related costs which increase with shift sizes. We also remark that, in previous research optimal sampling interval is observed to decrease with shift size for an EWMA mean chart (Park et al, 2004), which is in consistence with our results for the EWMA-m/EWMA-v scheme.…”
Section: Numerical Examplessupporting
confidence: 78%
“…The inverse relationship between the optimal sample size and the magnitude of the shift has also been observed in the economic design of X-bar charts (Montgomery, 1980). The results given in Park et al (2004) for EWMA mean charts also reveal a similar pattern. The reduction in sample size can be explained by the fact that large shifts in mean and/or variance can be detected more easily than small shifts, implying a reduced need for a large sample size.…”
Section: Numerical Examplessupporting
confidence: 63%
See 1 more Smart Citation
“…[18] Ho and Case [19] and Torng et al [20] explored the economic optimal design of EWMA control charts to monitor process shifts. Park et al [21] considered the economic design of the variable sampling rate EWMA control charts to determine the optimal parameter such that the expected total cost is minimized. Some authors have considered the production costs based on a quadratic loss function for economical design.…”
Section: Introductionmentioning
confidence: 99%
“…Designing and evaluating monitoring schemes using the ECU is usually referred to as the economic design of the scheme. The economic design of SPC control charts has been studied, for example, by Jiang and Tsui (2000), Lorenzen and Vance (1986), Montgomery (1980), Park and Reynolds (1999) and Park, Lee, and Kim (2004).…”
Section: Introductionmentioning
confidence: 99%